2020
DOI: 10.1001/jamanetworkopen.2020.28929
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Factors Associated With Chronic Pain 1 Year After Operative Management of Distal Radius Fractures

Abstract: Key Points Question What are modifiable preoperative factors associated with developing chronic pain after distal radius fracture surgery? Findings In this secondary analysis of a randomized clinical trial with 146 participants, each 10-point increase in preoperative pain score was associated with 17% increased odds of chronic pain, and a 1-week delay in surgical intervention was associated with more than triple the odds of experiencing chronic pain. Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…The significant differences in PROMs were found at a surgical delay of seven days or more and two different PROM tools were utilized, DASH 23,28 and The Michigan Hand Outcomes Questionnaire 16 . Clinical outcomes included increased finger and thumb stiffness (>2 wk delay), 20 decreased functional outcomes in flexion and ulnar deviation at a delay of greater than one week, 23 and more than triple the odds of experiencing chronic pain with a one-week delay to surgery 24 . One study found that surgeons reported greater procedural difficulty with a delay greater than one week 16 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The significant differences in PROMs were found at a surgical delay of seven days or more and two different PROM tools were utilized, DASH 23,28 and The Michigan Hand Outcomes Questionnaire 16 . Clinical outcomes included increased finger and thumb stiffness (>2 wk delay), 20 decreased functional outcomes in flexion and ulnar deviation at a delay of greater than one week, 23 and more than triple the odds of experiencing chronic pain with a one-week delay to surgery 24 . One study found that surgeons reported greater procedural difficulty with a delay greater than one week 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Time to surgery evaluated and the definition of delay varied by publication, with 13% of studies defining delay within one week of injury, 47% after one week, 27% after two weeks, and 13% after three weeks or longer (up to 25 days after injury). Only five (33%) of the included studies provided reasons for delay that included: administrative and capacity related reasons such as operating room availability, [21][22][23][24] delayed patient presentation, 21,22 and injury severity. 23,24,31 Trial Outcome Measures Ten (67%) trials found no significant difference in time to surgery as defined by delayed and non-delayed groups.…”
Section: Time To Surgery and Definition Of Delaymentioning
confidence: 99%
See 3 more Smart Citations